Systematic review of patients’ views on the quality of primary health care in sub-Saharan Africa - Daprim S Ogaji; Sally Giles; Gavin Daker-White; Peter Bower (SAGE Open Medicine, 2015)
This is the first systematic review of patient views on the quality of primary health care services in sub-Saharan Africa using studies identified from MEDLINE, CINAHL Plus, EMBASE and PsycINFO. In total, 20 studies (3 qualitative, 3 mixed method and 14 quantitative) were included. Meta-analysis was done using quantitative findings from facility- and community-based studies of patient evaluation of primary health care. There was low use of validated measures, and the most common scales assessed were humanness (70%) and access (70%). While 66% (standard deviation = 21%) of respondents gave favourable feedback, there were discrepancies between surveys in community and facility contexts. Findings suggest that patient views could vary with subject recruitment site. We recommend improvement in the methods used to examine patient views on quality of primary health care.